Synthesis, Characterization and Thermodynamic Properties of Two New 1,3-Dioxolane Containing Copolymers - Ilter, Zulfiye; Oncu, Ilbey; Karagoz, M. Hamdi; Ercan, Selami; Alhanli, Ferhat (Chem Soc Pakistan, 2016)
This study, reports the synthesis and characterization of two new copolymers (poly[2-(p-chlorophenyl)-1,3-dioxolane-4-yl] methyl acrylate-co-styrene (PCPhDMA-co-St) and poly[2-(p-chlorophenyl)-1,3-dioxolane-4-yl] methyl acrylate-co-acrylonitrile (PCPhDMA-co-AN)). Copolymers were characterized by spectral (FT-IR, H-1 - NMR) and thermal analysis (TGA, DSC). Their thermodynamic properties, such as the adsorption enthalpy, Delta H-a, molar evaporation enthalpy, Delta H-v, the sorption enthalpy, Delta H-1(s), sorption free energy, Delta G(1)(s), sorption entropy, Delta S-1(s), the partial molar free energy, Delta G(1)(infinity), the partial molar heat of mixing, Delta H-1(infinity), at infinite dilution were studied by inverse gas chromatography. Depending on specific retention volumes, V-g(0), of probes the weight activity coefficients of solute probes at infinite dilution, Omega(infinity)(1), and Flory-Huggins interaction parameters, chi(infinity)(1z) between PCPhDMA-co-St and PCPhDMA-co-AN-solvents were investigated in the range of 413-453 K and 403-453 K, respectively.
Keywords: Polymer; Polymer Synthesis; Thermodynamic properties; Inverse Gas Chromatography; Solubility parameters